Iodine-catalyzed, one-pot, three-component aza-Friedel-Crafts reaction of electron-rich arenes with aldehyde/carbamate combinations - Jaray Jaratjaroonphong (2018)
Iodine is shown to be an efficient catalyst for a one-step, three-component aza-Friedel-Crafts reaction of activated arenes or heteroarenes with benzyl or tert-butyl carbamates in combination with a wide variety of aldehydes in toluene under 'open-flask' and mild conditions. In the presence of 5 mol % of iodine in toluene at room temperature, the reaction gives the corresponding N-CBz or N-Boc protected α-branched amines, selectively, in good to excellent yields. © 2012 Elsevier Ltd. All rights reserved.